Study guides

Q: How answer this (12x-3) (12x 3)?

Write your answer...

Submit

Still have questions?

Continue Learning about Geometry

(2x - 3)3 = (2x - 3)(2x - 3)(2x - 3) = (4x2 - 12x + 9)(2x - 3) = 8x3 - 36x2 + 54x - 27

Assume the first piece to be x met. Then the second = 3x and the third =12x . Together, x + 3x + 12x = 64 or 16x = 64 or x= 4 met. The three pieces, therefore, are 4m, 12m and 48 m

If: x^2 +y^2 = 12x -10y -12 Then: x^2 +y^2 -12x +10y +12 = 0 Completing the squares: (x-6)^2 +(y+5)^2 = 49 which is the radius squared Center of circle: (6, -5) Diameter of circle: 14 units

A line in the X-Y plane follows an equation y = (slope X x) plus a constant k. In this instances, 5 = [(-12)(3)] + k, or k = 5 + 36 = 41. Therefore, the equation is: y = -12x + 41.

It is: x = 4.5 and so the acute angles are 36 degrees and 54 degrees

Related questions

x2 - 12x3 = x2(1 - 12x)

12x^3+17x^2+5x=0x(12x^2+17x+5)=0x(x+1)(12x+5)=0x=0x=-1x=-5/12

12x3 + 5y cannot be factored.

factor

The 3 is the factor

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

3. 7x3= 21 12x3= 36

8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5

It is: -3(4x-0.50) = -12x+1.50 or as 1.50-12x

5x-3 = 11+12x 5x-12x = 11+3 -7x = 14 x = -2

12x = x + 3 11x = 3 x = 3/11

12x - 8 = 10x + 42x = 12x = 6

People also asked